Hypokalemic Periodic Paralysis Triggered by Insulin Therapy in a Patient with Well-Controlled Type 2 Diabetes Mellitus: A Case Report - Helmi Aryosyaputra; Prenal L.M Ronsumbre; Lucas Julisar Selawa; Edwin Pranata Laban (Acta Neurologica Indonesia, 2026)
Introduction: Hypokalemic Periodic Paralysis (HPP) is a rare neuromuscular disorder characterized by acute, reversible muscle weakness associated with low serum potassium levels. It may occur due to genetic abnormalities or secondary causes, including insulin therapy, which remains an underrecognized trigger. Case Report: A 71-year-old man with well-controlled type 2 diabetes mellitus and hypertension presented with sudden bilateral lower limb weakness. Physical examination revealed flaccid paraparesis without sensory deficits. Laboratory findings showed hyperglycemia (320 mg/dL) and hypokalemia (K⁺ 2.96 mmol/L). The patient was on regular subcutaneous insulin therapy with no prior similar episodes. Muscle strength improved within 24 hours after oral potassium supplementation and metabolic correction. Discussion: Insulin promotes intracellular potassium shift through activation of the Na⁺/K⁺-ATPase, leading to acute hypokalemia and impaired skeletal muscle excitability. The absence of sensory deficits and rapid clinical improvement following potassium supplementation supported the diagnosis of secondary HPP. In elderly patients with multiple comorbidities, this presentation may mimic neurological disorders, making electrolyte evaluation crucial. Conclusion: HPP should be considered in diabetic patients receiving insulin who present with acute muscle weakness. Early recognition and prompt correction of hypokalemia are essential for rapid recovery and prevention of serious complications.